The effects of subchronic exposure to terbuthylazine on early developmental stages of common carp - Štěpánová, Stanislava; Plhalová, Lucie; Doleželová, Petra; Prokeš, Miroslav; Maršálek, Petr; Škorič, Miša; Svobodová, Zdeňka (TheScientificWorldJournal, 2012)
The aim of this study was to assess the impact of terbuthylazine in surface waters on fish under experimental conditions. Subchronic toxic effects on embryos and larvae of common carp (Cyprinus carpio) were investigated during a 30-day toxicity test. The exposure to terbuthylazin showed no effect on mortality, but significant differences (P < 0.0001) were revealed on weight and growth parameters at concentrations of 520 and 820 μg/L. The inhibition of specific growth rate at concentrations of 520 and 820 μg/L was 14% compared to the control group. No significant negative effects on total body length and body weight were observed at lower concentrations (0.9 and 160 μg/L). The concentrations 520 and 820 μg/L were associated with a delay in development compared to other experimental groups and controls. On the basis of weight and growth rate evaluation and determination of developmental stages, the No Observed Effect Concentration (NOEC) of terbuthylazine was estimated at 160 μg/L and the Lowest Observed Effect Concentration (LOEC) was 520 μg/L. According to these results, the reported environmental concentration of terbuthylazine in Czech rivers does not impact growth, development, morphology, or histology of carp embryos and larvae.
Keywords: triaziny; Carps; Dose-Response Relationship, Drug; herbicidy; vztah mezi dávkou a účinkem léčiva; Water Pollutants, Chemical; kapři; zvířata; Herbicides; míra přežití; Environmental Exposure; vystavení vlivu životního prostředí; Survival Rate; Triazines; chemické látky znečišťující vodu; Animals